Analisis Kawasan Rawan Bencana Kekeringan Menggunakan Sistem Informasi Geografis di Kabupaten Pesisir Selatan - Dwi Marsiska Driptufany; Nasyahardian Nasyahardian; Ilham Armi; Fajrin Fajrin; Defwaldi Defwaldi (Jurnal Sains dan Ilmu Terapan, 2025)
Drought is one of the natural disasters that significantly affects people's lives, particularly in terms of clean water availability and the agricultural sector. Pesisir Selatan Regency is an area prone to drought due to prolonged dry seasons and decreased rainfall. This study aims to identify the level of drought vulnerability and map the distribution of drought-prone areas in Pesisir Selatan Regency using a scoring method based on Geographic Information Systems (GIS). The parameters used in the analysis include land use, slope gradient, rainfall, soil type, and river networks. The data were obtained from administrative maps, spatial data, and hydrological and climatological information. The results show that most areas in Pesisir Selatan Regency fall into the moderate vulnerability category, while areas with high vulnerability are commonly found in residential and rice field zones. In contrast, areas with low vulnerability are located near water bodies and are highly influenced by high rainfall levels.